2013
DOI: 10.2500/ajra.2013.27.3936
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Complications Resulting from Dental Treatment: Outcome-Oriented Proposal of Classification and Surgical Protocol

Abstract: The results obtained are very encouraging. The majority of patients (254/257; 98.8%) were successfully treated with the proposed protocols. These results seem to indicate that the rationalization of surgical treatment protocols according to the initial clinical situation may significantly improve the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 28 publications
(41 reference statements)
2
120
0
3
Order By: Relevance
“…All patients underwent functional endoscopic sinus surgery (FESS) with the authors stating that large antrostomies are required especially in cases with implant dislocation (13% of cases in this study) and fungus ball removal [16]. Moreover, a modified EMM (MEMM) is described in combination with external approaches in cases involving the maxillary sinus floor, such as oroantral fistulas, and large odontogenic cysts [15,16].…”
Section: Key Pointsmentioning
confidence: 98%
See 1 more Smart Citation
“…All patients underwent functional endoscopic sinus surgery (FESS) with the authors stating that large antrostomies are required especially in cases with implant dislocation (13% of cases in this study) and fungus ball removal [16]. Moreover, a modified EMM (MEMM) is described in combination with external approaches in cases involving the maxillary sinus floor, such as oroantral fistulas, and large odontogenic cysts [15,16].…”
Section: Key Pointsmentioning
confidence: 98%
“…Felisati et al [16] in a large cohort included 257 consecutive patients with sinonasal complications resulting from dental treatment without response to medical treatment. All patients underwent functional endoscopic sinus surgery (FESS) with the authors stating that large antrostomies are required especially in cases with implant dislocation (13% of cases in this study) and fungus ball removal [16].…”
Section: Key Pointsmentioning
confidence: 99%
“…Fungus balls are not expected to respond to medical therapy;7 therefore, the patient was proposed an endoscopic surgical procedure, as proposed by Felisati et al 3. This approach was pivotal for healing of inflammatory and infectious process and also for the final anatomical pathology diagnosis.…”
Section: Treatmentmentioning
confidence: 99%
“…More modern and broader views on the subject showed that odontogenic sinusitis can follow all kind of dental procedures,3 with either unilateral or bilateral disease and mixed aerobe, anaerobe and mycotic infections,4–6 picturing definitely more complex scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Меха-ническое воздействие, а также цитотоксический и сенсибилизирующий эффекты, присущие практи-чески всем видам пломбировочных паст, приводят к воспалительным изменениям в синусе, пролифера-ции слизистой оболочки и гнойно-некротическим осложнениям [31,32].…”
Section: сведения об авторахunclassified